Agama: Sebuah Upaya Pembebasan Manusia (Perspektif-Dialogis Islam dan Kristen) - Munawir Muin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Contemporary issues are present in the course of human civilization. In this  part, religion should take its participation and offer a solution to these human contemporary issues. Religion should play an immense role solving the existing conflicts, but not serve as the source of conflicts. It is significant, in this context, to underscore religion as a solution of liberating human from their conflicts. The populist type of religiosity is demanding. It does not refer to place religiosity in its plain aim, but serves it as a medium pursuing the welfare of life. It leads to pluralist-liberalist traits that aware the truth outside one’s religion, support respects and tolerance to others in terms of their religious expressions.